(3JGL GdJQGLe aj WHbGJ GdMfajIs - (3bGSe Hf bWdhHZG, Rjf GdOjf, CHh GdYOd GdShOhfj GdLeGdj,J (B879 (3g` s ((3YeQ Hf CMeO Hf eMeO NdjaI Hf GdRcj GdMHj GdTGaYj GdSYOj s)
(3ChdgG (B:s
(3jbhd GdYHO GdVYja bGSe Hf bWdhHZG(B: (3CeG hbaJ Ydi JPcQI TjNfG TgGH GdOjf CMeO Hf Ydi GdebQjRi CeJY Gddg HMjGJg s
(3BNQgG (B:s
(3JQLeI GdjROj eSYhO Hf GdMSjf eef YSGg jTJgQ HfSH ChdbH s
(3GfXQ Qbe (B943(3JGQjNs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B111s
Keywords: (3GdJGQjNs